2014
DOI: 10.1186/1471-2474-15-50
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-synthesis of the impact of low back pain on people’s lives

Abstract: BackgroundLow back pain (LBP) is a common and costly problem that many interpret within a biopsychosocial model. There is renewed concern that core-sets of outcome measures do not capture what is important. To inform debate about the coverage of back pain outcome measure core-sets, and to suggest areas worthy of exploration within healthcare consultations, we have synthesised the qualitative literature on the impact of low back pain on people’s lives.MethodsTwo reviewers searched CINAHL, Embase, PsycINFO, PEDr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
327
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 338 publications
(347 citation statements)
references
References 80 publications
11
327
1
8
Order By: Relevance
“…Metaethnographies or meta-synthesis of such studies provide a useful comparator for the current study. The findings resonate with many of the themes discussed: the adversarial struggle to affirm self, explain pain, negotiate the healthcare system, and to be valued and believed; 25 the undermining and disempowering impact of pain, and unsatisfying relationships with healthcare providers; 26 difficulties with activities and stigma; 27 and the impact on self and relations with significant others. 28 The same studies find some evidence of moving forward with pain, accepting and adjusting, and changing outlook.…”
Section: Comparison With Existing Literaturesupporting
confidence: 55%
“…Metaethnographies or meta-synthesis of such studies provide a useful comparator for the current study. The findings resonate with many of the themes discussed: the adversarial struggle to affirm self, explain pain, negotiate the healthcare system, and to be valued and believed; 25 the undermining and disempowering impact of pain, and unsatisfying relationships with healthcare providers; 26 difficulties with activities and stigma; 27 and the impact on self and relations with significant others. 28 The same studies find some evidence of moving forward with pain, accepting and adjusting, and changing outlook.…”
Section: Comparison With Existing Literaturesupporting
confidence: 55%
“…Taking into account the widely accepted bio-psycho-social model for LBP [42,43], it may be appropriate to have a domain like 'health-related quality of life' in this COS as its definition includes all components of the model ( Table 2). The inclusion of all components of the bio-psycho-social model is also in line with the domains included in a conceptual framework developed to characterize the burden of LBP [35] and with the results of a review that attempted to summarize qualitative research conducted on the impact of LBP on people's lives [44]. However, it will be clear only when choosing measurement instruments for this COS if the different components of 'health-related quality of life' can be treated as separate domains or as one multidimensional domain.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of qualitative studies has also identified that current outcome measures may not be adequately capturing the social component of the impact of LBP. 156 Although the numbers in our study are limited, people appear to have been able to complete the adapted follow-up PGI score satisfactorily. The results show the expected improvement over time.…”
Section: Patient Generated Indexmentioning
confidence: 99%